AKTIVITAS ANTIOKSIDAN DARI DAUN BINTANGUR (Calophyllum inophyllum L.) TERHADAP RADIKAL BEBAS DPPH (1,1 Difenil-2-pikrihidrazil - Faisal, Ahmad Purnawarman; Nasution, Pratiwi Rukmana; Wakidi, Riza Fahlevi (Jurnal Riset Kefarmasian Indonesia, 2022)
Antioxidants are compounds that can inhibit oxidation reactions by binding to free radicals and highly reactive molecules. Bintangur contains saponins, tannins, flavonoids and alkaloids. In the presence of flavonoids, the purpose of this study is to understand the antioxidant activity of ethanol extracts against DPPH free radicals, and the IC50 parameter has the highest antioxidant activity. Use ethanol to macerate Bintangur leaf powder. Analyze the content of secondary metabolites in ethanol extracts. Use a spectrophotometer to test the antioxidant activity of the obtained extract against DPPH free radicals at a wavelength of 517 nm, and determine the IC50 value. Routine was used as a positive control in this study. The results of three repeated studies showed that the IC50 values ​​of the ethanol extract were 65.49 ppm, 65.76 ppm, and 65.76 ppm, respectively. Average IC50 value is 55.67 ppm.